Questions of preparing students for productive teaching of younger schoolchildren (Pedagogy of Higher and Secondary Education, 2014)
Balakireva V. Questions of preparing students for productive teaching of younger schoolchildren.The article presents the analysis of the process of preparing students for productive teaching of younger schoolchildren. The objectives and principles of effective teaching are reviewed, as well as the key position of teachers in the system of productive learning.
Keywords: productive learning; schoolchildren; younger schoolchildren; self-educational activity; productive training methods